2005
DOI: 10.1364/opex.13.004263
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of spectral changes for depth localization of fluorescent inclusion

Abstract: Abstract:We have performed modeling of fluorescence signals from inclusions inside turbid media to investigate the influence of a limited fluorescence contrast and how accurately the depth can be determined by using the spectral information. The depth was determined by forming a ratio of simulated fluorescence intensities at two wavelengths. The results show that it is important to consider the background autofluorescence in determining the depth of a fluorescent inclusion. It is also necessary to know the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…To retrieve the spatially varying regularization parameter, or regularization map, the fluorescence emission from the inclusion itself can be used. It has previously been reported that the intensity ratio of the fluorescence emission at two wavelengths, here denoted λ m1 and λ m2 , from a fluorescent inclusion detected at the boundary of the tissue is dependent on the depth of the inclusion [15,16]. This effect is due to the difference in bulk tissue attenuation, mainly absorption i.e.…”
Section: Spatial Priors Based On Fluorescence Emissionmentioning
confidence: 99%
“…To retrieve the spatially varying regularization parameter, or regularization map, the fluorescence emission from the inclusion itself can be used. It has previously been reported that the intensity ratio of the fluorescence emission at two wavelengths, here denoted λ m1 and λ m2 , from a fluorescent inclusion detected at the boundary of the tissue is dependent on the depth of the inclusion [15,16]. This effect is due to the difference in bulk tissue attenuation, mainly absorption i.e.…”
Section: Spatial Priors Based On Fluorescence Emissionmentioning
confidence: 99%
“…In the visible part of the spectrum this is due to the difference in bulk tissue attenuation, mainly influenced by the blood absorption 8 . This is experimentally shown in Fig.…”
Section: Fluorophore Region Confinementmentioning
confidence: 99%
“…The multispectral information provided in fluorescence measurements of lesions located at a certain depth in tissue would, in addition to the diagnostic information that there exist a lesion, also provide depth information useful for reconstruction of fluorescent inclusions in tissue [15,16]. This is one possible concept to improving the robustness and accuracy of the fluorescence tomography reconstructions.…”
Section: Time-of-flight Laser Spectroscopy In Biomedical Diagnosticsmentioning
confidence: 99%